Bioprospecting for Isoetes cangae Endophytes with Potential to Promote Plant Growth - Santos, Danielle Silveira; Pontes, Paula Veronesi Marinho; Leite, Analy Machado de Oliveira; Ferreira, Aline Lemos; Souza, Mariana de; Araujo, Thainá dos Santos Silva; Santos, Henrique Fragoso dos; Oliveira, Guilherme Correa de; Bitencourt, José Augusto; Cavalcanti, Allysson Buraslan; Martins, Rodrigo Lemes; Esteves, Francisco De Assis (International Journal of Microbiology, 2023)
Isoetes cangae is a native plant found only in a permanent pond in Serra dos Carajás in the Amazon region. Plant-associated microbial communities are recognized to be responsible for biological processes essential for the health, growth, and even adaptation of plants to environmental stresses. In this sense, the aims of this work were to isolate, identify, and evaluate the properties of endophytic bacteria isolated from I. cangae. The bioprospecting of potentially growth-promoting endophytes required the following steps to be taken: isolation of endophytic colonies, molecular identification by 16S rDNA sequence analysis, and evaluation of the bacterial potential for nitrogen fixation, production of indole acetic acid and siderophores, as well as phosphate solubilization and mineralization. Bacillus sp., Rhizobium sp., Priestia sp., Acinetobacter sp., Rossellomorea sp., Herbaspirillum sp., Heyndrickxia sp., and Metabacillus sp., among other bacterial species, were identified. The isolates showed to be highly promising, evidencing the physiological importance for the plant and having the potential to promote plant growth.